Development of edible films obtained from submicron emulsions based on whey protein concentrate, oil/beeswax and brea gum - Cecchini, Juan Pablo (2017)
Edible films with whey protein concentrate (WPC) with a lipid component, sunflower oil (O) or beeswax (W), to enhance barrier to water vapor were obtained. Brea gum was used as emulsifier and also as matrix component. In order to achieve emulsion with small and homogeneous droplet size, an ultrasonicator equipment was used after obtaining a pre-emulsion using a blender. The films were made by casting. Effects of lipid fraction on droplet size, zeta potential, mechanical properties, water vapor permeability (WVP), solubility, and optical properties were determined. The droplet size of emulsions with BG decreased when decreasing the lipid content in the formulation. The zeta potential was negative for all the formulations, since the pH was close to 6 for all of them and pI of BG is close to 2.5, and pI of ß-lactoglobulin and α-lactalbumin (main proteins in WPC) are 5.2 and 4.1, respectively. Increasing W or SO content in blended films reduced the tensile strength and puncture resistance significantly. BG and WPC films without lipid presented better mechanical properties. The presence of lipids decreased the WVP, as expected, and those films having BG improved this property. BG films were slightly amber as a result of the natural color of the gum. BG has shown to be a good polysaccharide for emulsifying the lipid fraction and improving the homogeneity and mechanical properties of the films with WPC and beeswax or oil.